1986
DOI: 10.1016/0378-1097(86)90022-4
|View full text |Cite
|
Sign up to set email alerts
|

The acetyl-CoA pathway of autotrophic growth

Abstract: The most direct conceivable route for synthesis of multicarbon compounds from CO: is to join two molecules of CO 2 together to make a 2-carbon compound and then polymerize the 2-carbon compound or add CO 2 successively to the 2-carbon compound to make multicarbon compounds. Recently, it has been demonstrated that the bacterium, Clostridium thermoaceticum, grows autotrophically by such a process. The mechanism involves the reduction of one molecule of CO 2 to a methyl group and then its combination with a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 97 publications
(86 reference statements)
0
58
0
Order By: Relevance
“…Green photosynthetic bacteria (the Chlorobiaceae) fix carbon mainly by reversing the tricarboxylic acid cycle (Sirevag et al, 1977). Together with nonphotosynthetic bacteria that can grow autotrophically while fixing carbon and constructing biomass by use of the "acetyl-CoA pathway" (i.e., acetogenic and methanogenic bacteria, Wood et al, 1986), they form a subset of organisms in which carbon is . Schematic views of the the differing pathways by which carbon is supplied to biosynthetic reaction networks.…”
Section: Fractionation Associated With Carbon Fixationmentioning
confidence: 99%
“…Green photosynthetic bacteria (the Chlorobiaceae) fix carbon mainly by reversing the tricarboxylic acid cycle (Sirevag et al, 1977). Together with nonphotosynthetic bacteria that can grow autotrophically while fixing carbon and constructing biomass by use of the "acetyl-CoA pathway" (i.e., acetogenic and methanogenic bacteria, Wood et al, 1986), they form a subset of organisms in which carbon is . Schematic views of the the differing pathways by which carbon is supplied to biosynthetic reaction networks.…”
Section: Fractionation Associated With Carbon Fixationmentioning
confidence: 99%
“…Two types of reactions have been recognized: reductive, to less-highly chlorinated methanes, and substitutive, to CO 2 and some of its transformation products [4][5][6]. The ability to anaerobically transform CCI 4 has been correlated [5] with the presence of the acetyI-CoA pathway [7,8] for the degradation or synthesis of acetate (acetyI-CoA) in these organisms. Bacteria with an operative acetyi-CoA pathway contain high levels of corrinoids [9.10], and it has been suggested that the latter catalyze reductive dehalogenation in anaerobic bacteria [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…In analogy to the role of the corrins in methanogens [4,40] and in acetogens [3,41], in this eubacterial sulfate reducer the rather abundant corrins presumably participate as Cop-methyl-derivatives in the crucial acetyl-CoA C-C bound-forming or cleavage steps. The high amounts of cobamides found in the eubacterium D. propionicus and in the archaebacterium A.fulgidus [30,31] also suggest a central role of the corrins in these sulfate reducers.…”
Section: Discussionmentioning
confidence: 99%